The Relationship Between Student Self-confidence, AI Support, and Academic Achievement: A Study in the Psychology of Motivation and Learning - Silitubun, Evaristus (Kuras Institute, 2023)
This research explores the relationship between student self-confidence, artificial intelligence (AI) support, and academic achievement in the psychology of motivation and learning. In this digital era, AI technology is increasingly used in education to facilitate teaching-learning. This research examines How AI support can affect students' self-confidence and how it affects their academic performance. Data are collected from 80 students at STPK ST. Yohanes Rasul Jayapura, Thomas Aquinas College of Agriculture 100 people, and Papua International University 20 people, 120 via questionnaire. The research results show that students' self-confidence and AI support are essential in improving academic performance. Implementing AI technology in education not only helps deliver lesson material but also contributes to improving students' self-confidence. Therefore, schools and institutions​ of education recommend using AI technology as a learning strategy to maximize potential student academics.